An Observational Case Series of Spinal Cord Stimulation Waveforms Visualized on Intraoperative Neuromonitoring. Issue 2 (29th April 2018) - Falowski, Steven M.
Abstract : Introduction: Intraoperative neuromonitoring for spinal cord stimulation uses electromyography (EMG) responses to determine myotomal coverage as a marker for dermatomal coverage. These responses are utilized to determine the orientation of the electrode. Somatosensory evoked potential (SSEP) collision testing can also be used in which sensory signals are decreased and/or eliminated when stimulation is activated. Methods: Fifteen patients were observed in the study. Each manufacturer had a minimum of three patients. Those included were Abbott BurstDR waveform, Boston Scientific burst stimulation, Medtronic high‐dose stimulation, and Nevro high‐frequency waveform. Efficacy of therapy was determined by a successful trial. Analysis performed during the permanent implant, included findings with traditional tonic stimulation, specific waveform and stimulation platforms, amplitude differences, and findings for both EMG responses and SSEP collision testing. Results: The Abbott BurstDR waveform produced the most findings. The amplitudes necessary to generate an observed EMG response were far lower than others, with a threshold of 10–20% of that seen in traditional tonic programming. The Medtronic high‐dose programming and Nevro high‐frequency waveform did not generate any observable EMG responses. Unique to Abbott BurstDR waveform was the onset of EMG activity in the distal muscle groups prior to proximal ones, as well as a hyperexcitability phenomenon acting as a primer generating signals at lower thresholds with more robust responses when returning to traditional tonic stimulation. EMG responses demonstrated propagation into one large EMG spike with BurstDR, while Boston Scientific burst stimulation had no propagation with separate spikes being consistent with traditional tonic stimulation. Conclusion: This observational series demonstrated distinct differences between the waveforms and stimulation alluding to different mechanisms of action. Nevro high‐frequency and Abbott BurstDR waveforms appear to be most different in action from traditional tonic stimulation while Abbotts BurstDR appears to be the most energy efficient generating signals at the lowest thresholds with a propagating effect that leads to a hyperexcitable or primed stimulation state.